0.4 V fully differential current conveyor using multiple-input bulk-driven MOST technique. (August 2019) - Kumngern, Montree
Abstract: This paper presents a new ultra-low voltage ultra-low power fully differential current conveyor (FDCCII) which is suitable for extremely low-voltage low-power analog signal circuit applications. Thanks to multiple-input bulk-driven MOS transistor technique, the proposed structure employs two differential pairs which offer low complexity and low power consumption. The bulk-driven MOS technique based circuit also provides rail-to-rail input common-mode range of proposed circuit. To prove the workability of the proposed FDCCII, the circuit has been used to realize summing/subtracting amplifier as design examples. The performances of the proposed FDCCII and design examples are demonstrated through PSPICE simulations using a 0.18 μm TSMC n-well CMOS process with 0.4 V supply voltage.